El régimen jurídico de la expropiación forzosa en el ordenamiento administrativo peruano. Evolución normativa y perspectivas actuales - Huapaya Tapia, Ramón Alberto (2016)
The forced expropriation has been, since the origins of the Peruvian Republic, a useful mechanism for the Government to meet its objectives, at the expense of the lawful damage inflicted to the private actors, conferring a fair compensation in return.In this article the current Peruvian legal regime of forced expropriation is studied, for which purpose both authors compare it with the regulation in the earliest Peruvian constitutions and laws, discovering that the concept has not always been designed in the same way by the constituent or the legislator.